Answer:
(-2, 5)
Step-by-step explanation:
we subtract 6x+3y=3 by 2x+3y=11 to get 4x=-8.
we divide both sides by 4 to get x. x=-2
We subsitute -2 for the second equation to get:
2(-2)+3y=11
=-4+3y=11
=3y=15
y=5
Answer:
D and C
Step-by-step explanation:
<span>This is the term used to describe economic systems in which the basic economic questions are answered based on a socially, pre-established way.</span>
Answer:
m=5
Step-by-step explanation:
c=30m+50
c=20m+100
substitute
20m+100=30m+50
like terms
100-50=30m-20m
50=10m
m=5
I think is is:
7/20=35/100=0.35=35%
Hope I'm not wrong!
Hope this helps! :D